Obturator hernia: A diagnostic dilemma, report of a case [Obturator herni̇: Tanisal i̇ki̇lem, bi̇r olgu sunumu] - (:unkn) unknown (Geriatrics Society, 2014)
Obturator hernia is a rare pelvic hernia that occurs in elderly, thin, multiparous women. Patients present with few nonspecific clinical symptoms to identify the cause, and the diagnosis is often delayed or missed. Physicians should maintain a high level of clinical suspicion for obturator hernia in elderly women as it is a diagnostic challenge in which the hernia mass is usually concealed beneath the pectineus muscle. Early diagnosis and prompt initiation of treatment reduces the risk of surgical complications and increases the chance of survival. Different imaging modalities including Ultrasound, herniography and CT have been proposed to assist with accurate diagnosis. Herein, we present a case of a 78 year-old woman with thigh pain secondary to an obturator hernia and magnetic resonance imaging confirmed the diagnosis.
Keywords: Hernia; Magnetic resonance imaging; Obturator; Pain